2016
DOI: 10.1128/aac.00426-15
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Antileishmanial Aziridine-2,3-Dicarboxylate-Based Inhibitor with High Selectivity for Parasite Cysteine Proteases

Abstract: L eishmaniasis is one of the 17 neglected tropical diseases (NTDs) assigned by the World Health Organization (WHO). NTDs affect 1 billion people worldwide (1). The primary occurrences are in low-income countries in sub-Saharan Africa, Asia, and Latin America, but the Mediterranean countries of Europe are also concerned (2). Among the NTDs is the group of "most neglected diseases," affecting the poorest, mainly rural areas, including leishmaniases, sleeping sickness (African trypanosomiasis), and Chagas' diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…To discriminate between host and parasite CPs, more selective inhibitors were synthesized based on both compounds. Compound s9 showed selective inhibitory potency against L. major CPC and L. mexicana CPB2.8, but not against mammalian CATHs B and L. It showed excellent IC50 against L. major promastigotes and amastigotes in vitro [103] .…”
Section: Cysteine Proteinase Inhibitors (Cpis)mentioning
confidence: 95%
“…To discriminate between host and parasite CPs, more selective inhibitors were synthesized based on both compounds. Compound s9 showed selective inhibitory potency against L. major CPC and L. mexicana CPB2.8, but not against mammalian CATHs B and L. It showed excellent IC50 against L. major promastigotes and amastigotes in vitro [103] .…”
Section: Cysteine Proteinase Inhibitors (Cpis)mentioning
confidence: 95%
“…Schad et al reported a new class of antileishmanial aziridine-2,3-dicarboxylate-based synthetic peptides as inhibitors of cysteine proteases (CPs) in Leishmania major ( L. major ) parasite. 61 L. major causes leishmaniasis and is wide spread in low-income countries in sub-Saharan Africa, Asia, and Latin America. According to the World Health Organization (WHO), leishmaniasis is among the 17 neglected tropical diseases (NTDs).…”
Section: Nitrogen Containing Saturated Heterocycles In Peptidomimeticsmentioning
confidence: 99%
“…These include peptide‐based inhibitors bearing an electrophilic warhead that covalently traps the catalytic thiolate such as dipeptidyl vinyl sulfone 1 , dipeptidyl α‐ketoheterocycles 2 and aziridinyl peptides (e.g. 3 ), semicarbazone 4 , thiosemicarbazones 5 , triazine nitrile 6 , natural compounds (e.g. morelloflavones 7 ), and a decorated fused benzo[ b ]thiophene inhibitor 8 acting through a time‐dependent bimodal mechanism of action (Figure ) …”
Section: Introductionmentioning
confidence: 99%